2021
DOI: 10.1038/s41598-021-85750-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional profiling of COVID-19 respiratory tract microbiomes

Abstract: In response to the ongoing global pandemic, characterizing the molecular-level host interactions of the new coronavirus SARS-CoV-2 responsible for COVID-19 has been at the center of unprecedented scientific focus. However, when the virus enters the body it also interacts with the micro-organisms already inhabiting the host. Understanding the virus-host-microbiome interactions can yield additional insights into the biological processes perturbed by viral invasion. Alterations in the gut microbiome species and m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…We suggest conducting a longitudinal study in which nasal samples are collected from healthy individuals and COVID-19 patients (both symptomatic and asymptomatic) and used for microbiome profiling via sequencing and metatranscriptomics. Functional analyses could distinguish the pathways associated with different disease states, including metabolites that serve as biomarkers ( 19 ). From these data, a target VOC signature could be identified and used in breath-based diagnostic tools with great impact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest conducting a longitudinal study in which nasal samples are collected from healthy individuals and COVID-19 patients (both symptomatic and asymptomatic) and used for microbiome profiling via sequencing and metatranscriptomics. Functional analyses could distinguish the pathways associated with different disease states, including metabolites that serve as biomarkers ( 19 ). From these data, a target VOC signature could be identified and used in breath-based diagnostic tools with great impact.…”
Section: Discussionmentioning
confidence: 99%
“…The effect SARS-CoV-2 infection has on the upper respiratory microbiome is less known. Haiminen et al ( 19 ) compared COVID-19 patients to healthy peers and to non-COVID-19-related pneumonia patients. After successfully differentiating patient groups by microbiome composition, they detected significant changes in bacterial metabolism pathways ( 19 ).…”
Section: Targeting Microbial Changes In the Nasal Cavity As A Methods For Early Sars-cov-2 Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions of the host with the microbiota are complex, numerous and bidirectional [ 59 ]. Therefore, the virus–host–microbiome interactions can yield further insights into the perturbed biological processes and their connections with disease risk factors [ 60 ]. Shen et al .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that SARS-CoV-2 infection alters the microbiome of the lung and leads to reduced diversity and in some cases to community collapse [61], shows different bacterial diversity and fewer commensals compared to non-COVID-19 pneumonia [62], and on a functional analysis "decreased potential for lipid metabolism and glycan biosynthesis and metabolism pathways, and increased potential for carbohydrate metabolism pathways" [63]. There is crosstalk between the gut and the lung, often referred to as the "gut-lung axis".…”
Section: Sars-cov-2 and The Gut Microbiomementioning
confidence: 99%